Industrial training report: Hospital Canselor Tuanku Muhriz (HCTM) / Nisa Afiqah Iskandar - Iskandar, Nisa Afiqah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report summarizes my industrial training experience at Hospital Canselor Tuanku Muhriz (HCTM), where I actively participated in various public health initiatives, events, and projects. Throughout the internship, I gained valuable skills in event management, graphic design, video editing, and communication. Notable contributions included organizing and managing activities such as the IKMAS program and the 10th International Public Health Conference. This experience enhanced my technical proficiency, work ethics, and professional skills, while also deepening my understanding of public health practices and healthcare operations.